Glycemic control in people with type 1 diabetes using a hybrid closed loop system and followed by telemedicine during the COVID-19 pandemic in Italy. (November 2020) - Longo, Miriam; Caruso, Paola; Petrizzo, Michela; Castaldo, Filomena; Sarnataro, Annalisa; Gicchino, Maurizio; Bellastella, Giuseppe; Esposito, Katherine; Maiorino, Maria Ida
Abstract: Aims: This study aims at evaluating the metrics of glycemic control in people with type 1 diabetes using the hybrid closed loop (HCL) system during the COVID-19 lockdown. Methods: This is a retrospective study of thirty adults with type 1 diabetes using HCL and followed with telemedicine at an Italian University Hospital. Data on metrics of glucose control were collected at different times: two weeks before the lockdown (Time 0), first two weeks of lockdown (Time 1), last two weeks of lockdown (Time 2) and first two weeks after the lockdown (Time 3). The primary endpoint was the change in glucose management indicator (GMI) across the different time points. Results: GMI did not worsen over time (Time 1 vs Time 3, 7% vs 6.9%, P < 0.05), whereas a reduction of mean glucose (P = 0.004) and indices of glucose variability was observed. Time in range (TIR) significantly increased (68.5% vs 73.5%, P = 0.012), and time above range (TAR) level 2 (251–400 mg/dL) significantly decreased (P = 0.002). The improvement of TIR and glucose variability was mainly observed in participants < 35 years. Conclusions: Adults with type 1 diabetes using HCL showed a significant improvement of most of the metrics of glucose control during the COVID-19 lockdown.